Effects of intermolecular interactions on the stability of carbon nanotube–gold nanoparticle conjugates in solution - Konczak L (Dove Medical Press, 2016)
Lukasz Konczak,1 Jolanta Narkiewicz-Michalek,2 Giorgia Pastorin,3 Tomasz Panczyk1 1Institute of Catalysis and Surface Chemistry, Polish Academy of Sciences, Cracow, 2Department of Chemistry, Maria Curie-Sklodowska University, Lublin, Poland; 3Department of Pharmacy, National University of Singapore, Singapore Abstract: This work deals with the role of intermolecular interactions in the stability of a carbon nanotube (CNT) capped by functionalized gold nanoparticles (AuNPs). The importance of such a system is due to its potential application as a pH-controlled drug carrier. Our preliminary experimental studies showed that fabrication of such a nanobottle/nanocontainer is feasible and it is possible to encapsulate the anticancer drug cisplatin inside the inner space of a CNT and seal its ends by functionalized AuNPs. The expected behavior, that is, detachment of AuNPs at acidic pH and the release of cisplatin, was, however, not observed. On the other hand, our theoretical studies of chemically identical system led to the conclusion that the release of cisplatin at acidic pH should be observed. Therefore, in this work, a deeper theoretical analysis of various factors that could be responsible for the disagreement between experimental and theoretical results were performed. The study found that the major factor is a large dispersion interaction component acting between CNT and AuNP in solution in the case of the experimental system. This factor can be controlled to some extent by tuning the system size or the ratio between AuNP diameter and CNT diameter. Thus, such kind of a pH-sensitive drug carrier is still of great interest, but its structural parameters need to be properly adjusted. Keywords: hydrazone bond, drug delivery, dispersion interactions, cisplatin, acidic pH